Android-Based Driving Course Information System - Elianti, Ni Made Dewik; Githa, Dwi Putra; Susila, A. A. Ngurah Hary (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 10 No 1 (2022): Vol. 10, No. 1, April 2022, 2021)
In the current era, technology development is required in society and has been used worldwide. Technology also has an important role in a company. Driving Courses Company is one of the companies that can compete in technology as it offers services to its customers. Many Driving Course companies do the business process conventionally and have no particular strategy for dealing with customers. The research method was conducted by collecting the data through direct interviews with informants, observing and analyzing related articles or journals. This study aimed to design and develop an Android-based driving course information system. It is expected to ease the business process and provide benefits for the company and customer. The result of the study is an Android-based Driving Course Information System which consists of some features, such as registration, scheduling, report, and location features. Those facilities are used to facilitate and ease the driving course business processes. Keywords: Information Systems, Android, Mobile, Scheduling, Routes